2018
DOI: 10.1556/2006.7.2018.131
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relationships between problem gambling, scratch card gambling, and individual differences in thinking style

Abstract: Background and aimsScratch cards are a popular form of lottery gambling available in many jurisdictions. However, there is a paucity of research that examines associations between individual differences in thinking style, participation in scratch card gambling, and problem gambling severity.MethodsIn three studies, we sought to examine the relationships among these variables in large, online samples of participants. Participants completed the Cognitive Reflection Test (CRT), the Problem Gambling Severity Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Research on unclaimed prize information suggests that it may be of high intuitive appeal (Walker et al, 2019), which may be one mechanism explaining its persuasiveness and resulting influence on gamblers' perceptions of scratch card games. Of course, another aspect of unclaimed prize information is that it is commonly judged as diagnostic when it is in fact not (Stange et al, 2018;Walker et al, 2019Walker et al, , 2018. This may make the influence of unclaimed prize information especially problematic from a harm reduction stand-point as utilizing this information does not improve gamblers' scratch card preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on unclaimed prize information suggests that it may be of high intuitive appeal (Walker et al, 2019), which may be one mechanism explaining its persuasiveness and resulting influence on gamblers' perceptions of scratch card games. Of course, another aspect of unclaimed prize information is that it is commonly judged as diagnostic when it is in fact not (Stange et al, 2018;Walker et al, 2019Walker et al, , 2018. This may make the influence of unclaimed prize information especially problematic from a harm reduction stand-point as utilizing this information does not improve gamblers' scratch card preferences.…”
Section: Discussionmentioning
confidence: 99%
“…This discovered 'superiority' of a subset of scratch card games may not only lead to gamblers preferring these games, but result in the increased appeal of these games overall, compared to if no unclaimed prize information was presented. The consequences of this increased appeal would not be trivial: despite the widespread notion that scratch cards are not harmful, recent research suggests that the frequency with which individuals engage in scratch card gambling is related to problem gambling severity (Stange et al, 2018). Additionally, reports of problematic scratch card use have been cited among both adults and adolescents (Raposo-Lima et al, 2015;Wood & Griffiths, 1998).…”
mentioning
confidence: 99%
“…Specifically, when presented with three otherwise identical scratch card games, participants felt more likely to win, were more excited to play, and preferred to hypothetically purchase the scratch card game with the greatest number of unclaimed prizes. Additionally, a majority of participants reported that they would be willing to pay to obtain unclaimed prize information, demonstrating that they valued this information despite its lack of utility (Stange et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…24 Finally, reliable associations between scratch card frequency and problem gambling severity have been reported in online samples. 25 Although near-miss outcomes in scratch card games have been shown to reliably increase the urge to continue gambling, and have been found to be associated with gambling harm in many jurisdictions, virtually no empirical research has examined the impact of scratch card nearmisses on players who are experiencing gambling harm. So far, laboratory-based scratch card studies have only used samples of undergraduate students, who despite having experience with scratch cards, typically report lower levels of problem gambling severity than the general population.…”
Section: Connections To Gambling-related Harmmentioning
confidence: 99%